Dynamic Response of Seismic Dangerous Rock Based on PFC and Dynamics - Yun Tian; Linfeng Wang; Honghua Jin; Biao Zeng (Advances in Civil Engineering)
Rock slope instability by earthquakes results in substantial economic and property losses. The calculation method of interlayer load and stability coefficient of horizontal complex layered rock slopes in high-intensity areas is established from material mechanics, fracture mechanics, and dynamics. The stability of horizontal layered dangerous rock is calculated after combining it with PFC simulation technology to verify the rationality of the calculation in the Wenchuan area of Sichuan Province. The dynamic response characteristics of dangerous rocks under different weathering degrees are also analyzed. The results show that both methods have an excellent early warning effect on earthquake dangerous rocks. Among the PGA amplification factors, Model 1 has a relatively uniform distribution, Model 2 has a zigzag distribution, Models 3 and 4 have a “U”-shaped distribution, and the most severe acceleration dynamic responses are 4-1 and 4-2 rock blocks. The dynamic acceleration response of mudstone is affected by the crack propagation process of the upper sandstone and exhibits a particular elevation amplification effect. The peak stress gradually decreases with the increase in weathering and elevation. The stress change of the inner chain No. 2 in the horizontal x and y directions is severe, and the stress response of the outer chain No. 1 in the vertical z-direction is severe. It recommends that earthquake disaster protection projects should pay attention to the impact of low-frequency (0–10 Hz) and high-frequency (250 Hz) earthquakes on slope stability.